Challenges Faced by The MSMEs: Input to Policy Recommendations - Manalo , Anna Liza H.; Balanay, Michael Q.; Verdadero, Joan Camille A. (International Journal of Basic and Applied Sciences, 2025)
MSMEs play a vital role in economic growth by stimulating employment, promoting revenue distribution, and reducing poverty. MSMEs operate but struggle ‎to compete with larger industries in terms of productivity. This study examined the challenges hindering the growth and performance of MSMEs, ‎aligning with the Sustainable Development Goals (SDGs) to support them, and addressed a critical research gap in localized MSME policy ‎interventions. This research uniquely focused on the specific socio-economic and regulatory conditions that contribute more to a targeted ‎approach for MSMEs. The study employed a descriptive survey with a researcher-made questionnaire, and 303 respondents were selected ‎through simple random sampling. Data analysis utilized percentages, means, Chi-square tests, and ANOVA. Findings indicated that most MSMEs ‎are sole proprietorships engaged in trading, with limited access to finance, technology, and market opportunities. The most pressing concern ‎remains the business environment, particularly regulatory inefficiencies and limited government support. The study revealed significant relationships between business type and business environment, business form, number of employees, years in operation, gross annual revenue, access to finance, access to technology, productivity, and efficiency. The study provided policy recommendations to enhance MSME resilience and align with the Sustainable Development Goals (SDGs), particularly SDG 8 (Decent Work and Economic Growth) and SDG 9 (Industry, Innovation, and Infrastructure).
Keywords: Access to Finance; Access to Market; Access to Technology; Business Environment; Productivity and Efficiency